Motivating others (American Management Association, 1992)
This video demonstrates a concrete set of guidelines to help managers elicit superior performance from their employees. Each FYI video presents an in-depth look at a specific managerial topic. It will gain dozens of lively ideas, useful tips, and expert insights through a stimulating newsmagazine format designed to help you enrich and improve your management skills and abilities.